Employer disability practice in Britain: assessing the impact of the Positive About Disabled People 'Two Ticks' symbol. (June 2014) - Hoque, Kim; Bacon, Nick; Parr, Dave
This article assesses the extent to which employers displaying the Positive About Disabled People 'Two Ticks' symbol adhere to the five commitments they are expected to uphold and whether adherence to these commitments is greater in Two Ticks than non-Two Ticks workplaces. It also assesses levels of employer support for and dialogue with Disability Champions in Two Ticks workplaces. These issues are explored in the public and private sectors separately. The analysis finds only limited adherence to the five commitments in Two Ticks workplaces, no consistent evidence that adherence is higher in Two Ticks than non-Two Ticks workplaces and limited evidence of support for and dialogue with Disability Champions in Two Ticks workplaces. It also finds little evidence of variation between public and private sector workplaces.